PEMBENTUKAN PERDAGANGAN BEBAS ASEAN-CHINA (ASEAN-CHINA FREE TRADE AREA) DAN DAMPAKNYA BAGI PETANI DI INDONESIA - Indriastuti, Suyani (MEDIAGRO, 2005)
Recently, free trade is a global phenomenon where the regions effort to make an exclusive free trade area. The Association of  South East Asian Nations (ASEAN) and China signed a comprehensive economic partnership agreement  on the teenth of ASEAN summit. The parties agreed  to strenghthen their coorperation in many sectors which the one of that  was agriculture sector. So Indonesian as  ASEAN member has enthusiasm to apply this agreement. It has many impacts for Indonesian farmer.Key word : Free trade, agriculture,Indonesian  farmer